2018
DOI: 10.21032/jhis.2018.43.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers’ Opinions on Digital Healthcare Services

Abstract: This paper presents a case study on security and privacy implications on the design of a mobile application in digital health, the DeStress Assistant (DeSA) app, which utilizes sensing technologies and capabilities of the Internet of Things (IoT). An analysis of the applicable legislative framework is provided and selected challenges encountered during the app design are discussed, which are related with the practical implications of provisions of the international and national legislation for software applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The development of technology and new machines can reduce nurses’ tasks, but nurses have to deal with the psychological burden of learning to operate them [ 7 ]. Nurses’ awareness and understanding of digital healthcare are lower than those of other health workers’ [ 8 ]. One study found that the telemedicine awareness of nursing students and the general public was more positive than that of nurses in Korea [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of technology and new machines can reduce nurses’ tasks, but nurses have to deal with the psychological burden of learning to operate them [ 7 ]. Nurses’ awareness and understanding of digital healthcare are lower than those of other health workers’ [ 8 ]. One study found that the telemedicine awareness of nursing students and the general public was more positive than that of nurses in Korea [ 9 ].…”
Section: Introductionmentioning
confidence: 99%